Incidental findings in pre‐orthodontic treatment radiographs (2020)
Objectives To determine the frequency, radiodensity characteristics, topographic location and number per patient of incidental findings observed in radiographs taken before orthodontic treatment and to evaluate the relationship of the findings with age and sex. Methods This was a cross‐sectional study that investigated 1,887 panoramic and lateral cephalogram radiographs from 783 patients (23.31 ± 13.11 years of age; 453 women and 330 men) who were randomly selected from the orthodontics department of a private university. The images were systematically evaluated by an oral pathologist. A chi‐square test was applied to evaluate the association between sex and the presence of pathology, radiodensity characteristics and topographic location. The Mann–Whitney U and Kruskal–Wallis tests were used to establish the association between age or number of findings per patient with other variables in the study. Results The prevalence of incidental findings was 88.12%. The most frequent finding was maxillary sinus pneumatisation (25.80%). No significant association was detected between frequency or number of findings per patient and either sex or diagnostic hypothesis. A significant association was found between age and the presence of pathology and number of incidental findings per patient (P < 0.001), as well as between the type of radiographic image and incidental finding (P < 0.001). Conclusion The prevalence of incidental findings in the sample studied was high, and the structures most commonly involved were the maxillary sinuses. The results suggest that both the presence and the number of findings per patient increase with age but there is no association with sex.